The case for cyber foraging - BALAN, Rajesh (Institutional Knowledge at Singapore Management University, 2002)
In this paper, we propose cyber foraging: a mechanism to augment the computational and storage capabilities of mobile devices. Cyber foraging uses opportunistically discovered servers in the environment to improve the performance of interactive applications and distributed file systems on mobile clients. We show how the performance of distributed file systems can be improved by staging data at these servers even though the servers are not trusted. We also show how the performance of interactive applications can be improved via remote execution. Finally, we present VERSUDS: a virtual interface to heteregeneous service discovery protocols that can be used to discover these servers.